2013
DOI: 10.1136/bmjopen-2013-002857
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two types of macrolide antibiotics for the purpose of assessing population-based drug interactions

Abstract: ObjectiveClarithromycin strongly inhibits enzyme cytochrome P450 3A4, preventing the metabolism of some other drugs, while azithromycin is a weak inhibitor. Accordingly, blood concentrations of other drugs increase with clarithromycin coprescription leading to adverse events. These macrolide antibiotics also differ on other properties that may impact outcomes. In this study, we compared outcomes in two groups of macrolide antibiotic users in the absence of potentially interacting drugs.DesignPopulation-based r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
0
22
1
1
Order By: Relevance
“…Interestingly, the risk of mortality also was substantially higher with clarithromycin than azithromycin coprescription with a CCB, with an NNH of 231. An earlier study 9 from this same group found that clarithromycin compared to azithromycin, not restricted to coadministration with a CCB, also was associated with a higher risk of death, but not with AKI. The extent to which the clarithromycin-alone effect confounds the findings by Gandhi et al 5 on AKI is not clear.…”
Section: What Does This Important Study Show?mentioning
confidence: 89%
“…Interestingly, the risk of mortality also was substantially higher with clarithromycin than azithromycin coprescription with a CCB, with an NNH of 231. An earlier study 9 from this same group found that clarithromycin compared to azithromycin, not restricted to coadministration with a CCB, also was associated with a higher risk of death, but not with AKI. The extent to which the clarithromycin-alone effect confounds the findings by Gandhi et al 5 on AKI is not clear.…”
Section: What Does This Important Study Show?mentioning
confidence: 89%
“…El potencial riesgo de interacciones con azitromicina se presentó en el 5,1 % de los pacientes del estudio, pero se ha observado que puede darse hasta en el 21,3 % de casos de pacientes con enfermedades cardiovasculares, en ambientes hospitalarios, o en pacientes con infecciones respiratorias (21,22). Pese a que las prevalencias de potencial riesgo son mayores en otros estudios, las razones pueden ser explicadas por las diferencias en las poblaciones estudiadas, y en este caso al ser sobre una base poblacional, pueden ser muy heterogéneas, lo que hace necesario aumentar esfuerzos investigativos, para la detección de interacciones en grupos de riesgo especial (21,22).…”
Section: Discussionunclassified
“…10,30,31 In a previous study of provincial data, we showed that clarithromycin and azithromycin have similar indications, clinical use patterns and rates of adverse events when used independently. 32 Thus, we felt that the comparison of outcomes among older adults prescribed these antibiotics would serve as a useful model for studying drug interactions in routine clinical practice.…”
Section: Study Populationmentioning
confidence: 99%